From program strategic planning to program initiation: lessons learned from a collaborative university-industry R&D case study - Fernandes, Aldora Gabriela Gomes (2019)
This paper aims to contribute to knowledge by presenting the lessons learned resultant from a large case study composed by three collaborative University-Industry RD funded programs between the University of Minho (UMinho) and Bosch Car Multimedia Portugal (Bosch). The three programs selected amount to a total investment of above €109 million, over the period between 2013 and 2021, involving more than one thousand University researchers and Industry collaborators. The lessons learned are limited to the time span from Program Strategic Planning, where new project ideas/innovation opportunities are identified and developed for the preparation of the 'Funding Application', to Program Initiation, where the program effectively initiates after the negotiation of the 'Funding Contract'. The collection, analysis and implementation of lessons learned allowed the development of a structured process to guide University-Industry partners on the path to transform some newly identified project ideas into the initiation of a large RD funded program. The proposed process is currently adopted by the governance structure of Bosch and UMinho partnership and other UMinho partnerships with Industry.